Genetic causality between insomnia and specific orthopedic conditions: Insights from a two-sample Mendelian randomization study - Mingyi Yang; Jiale Xie; Yani Su; Ke Xu; Pengfei Wen; Xianjie Wan; Hui Yu; Zhi Yang; Lin Liu; Peng Xu (Experimental Gerontology, 2025)
Objective: To investigate the genetic causality for the insomnia and common orthopedic diseases, such as rheumatoid arthritis (RA), ankylosing spondylitis (AS), osteoporosis (OP), and gout (GT). Methods: The genome-wide association study (GWAS) summary data on insomnia were obtained from a published study, while the GWAS summary data on RA, AS, OP, and GT were sourced from the FinnGen consortium. We utilized the TwoSampleMR package of the R software (version 4.1.2) to conduct a two-sample Mendelian randomization (MR) analysis. Our primary method of analysis was the random-effects inverse variance weighted (IVW) approach. Subsequently, we conducted a series of sensitivity analyses for the MR analysis. Results: The MR analysis revealed a positive genetic causal relationship between insomnia and RA (P = 0.016, odds ratio [OR] 95 % confidence interval [CI] = 1.112 [1.020–1.212]). However, no significant genetic causal relationship was observed between insomnia and AS (P = 0.194, OR 95 % CI = 1.121 [0.944–1.331]), OP (P = 0.788, OR 95 % CI = 1.016 [0.904–1.142]), and GT (P = 0.757, OR 95 % CI = 1.018 [0.912–1.136]). The MR analysis did not exhibit heterogeneity, horizontal pleiotropy, outlier effects, or dependence on a single SNP, and demonstrated normal distribution, which guaranteed the robustness of the results. Conclusion: The results of this study suggest that insomnia may be a significant risk factor for RA, and controlling insomnia may represent a promising strategy for preventing RA. While insomnia was not observed to be associated with AS, OP, and GT at the genetic level, other levels of association cannot be excluded.